Design improvement of cerebral palsy easy carrier - Nurhaslina Hashim (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This project was to design and improve a cerebral palsy child easy carrier used when travelling in a vehicle. A seating support which is backrest equip with 5 point harness belt are the main component in this design. The main reason for designing this carrier is because there is no such equipment in Malaysia which allows children with cerebral palsy to travel in high safety measure either for a short or long period of travel. This lead to the main purpose of this project is to design a product with high safety features with affordable price and to develop a product which is portable and easy to use.